Representing system by gene encoding - Bani Hashim, Ahmad Yusairi (Science Academy Publisher, 2011)
The chromosomes that belong to the parents store genetic information. The child inherits the information through uniquely selective procedures. Using the concept, this study proposes an approach to system representation using the process found in genetic information inheritance. A generic process flow to building the representation is shown in the form of ladder-like flow chart that has the starting point at the bottom. This forms the basis for gene encoding. Following this process flow, one can expect to represent a system which requires solutions from selective procedures. Therefore, the codes written may vary depending on how one models and interprets the representation.